Changes in brazilian higher education in view of regional development (Research, Society and Development, 2020)
The study aims to elucidate the changes promoted by MEC in Brazilian higher education, bringing them closer to the discussions about regional development. To achieve this purpose, it describes three specific changes in higher education, such as its aims, the number of vacancies increased in countryside; and the regulation process of educational institutions from the Federal State. Thereby, it’s connecting different authors’ ideas about regional development in Brazil. Throughout a bibliographic and documentary research, in an exploratory level, it concludes that those changes mentioned are prescribed by leading authors. This research results bring the hypothesis about the influence of such events in regional development.